Integrins regulate centrosome integrity and astrocyte polarization following a wound. Issue 5 (9th April 2013) - Peng, Huashan; Ong, Yen May; Shah, Waris Ali; Holland, Paul C.; Carbonetto, Salvatore
<x xml:space="preserve">Abstract</x> In response to a wound, astrocytes in culture extend microtubule‐rich processes and polarize, orienting their centrosomes and Golgi apparatus woundside. β1 Integrin null astrocytes fail to extend processes toward the wound, and are disoriented, and often migrate away orthogonal, to the wound. The centrosome is unusually fragmented in β1 integrin null astrocytes. Expression of a β1 integrin cDNA in the null background yields cells with intact centrosomes that polarize and extend processes normally. Fragmented centrosomes rapidly assemble following integrin ligation and cell attachment. However, several experiments indicated that cell adhesion is not necessary. For example, astrocytes in suspension expressing a chimeric β1 subunit that can be activated by an antibody assemble centrosomes suggesting that β1 activation is sufficient to cause centrosome assembly in the absence of cell adhesion. siRNA knockdown of PCM1, a major centrosomal protein, inhibits cell polarization, consistent with the notion that centrosomes are necessary for polarity and that integrins regulate polarity via centrosome integrity. Screening inhibitors of molecules downstream of integrins indicate that neither FAK nor ILK is involved in regulation of centrosome integrity. In contrast, blebbistatin, a specific inhibitor of non‐muscle myosin II (NMII), mimics the response of β1 integrin null astrocytes by disrupting centrosome integrity and cell polarization. Blebbistatin also inhibits integrin‐mediated centrosome assembly in astrocytes attaching to fibronectin, consistent with the hypothesis that NMII functions downstream of integrins in regulating centrosome integrity. © 2012 Wiley Periodicals, Inc. Develop Neurobiol 73: 333–353, 2013.